Are You Man Enough to do This Job? The Impact of Applicant Gender and Sexual Orientation on Screening Decisions - Pyatt, Jodie L.; Bartels, Lynn K. (Journal of Organizational Psychology, 2018)
Participants viewed application materials of one of four job candidates (i.e., heterosexual male or female, lesbian or gay man) for a male-typed job. Then, participants rated the applicant on agency and communality and made hiring and salary recommendations. Lesbians were perceived as more agentic (e.g., dominance, confidence) than heterosexual women and gay men. Agency was a predictor of hiring and salary outcomes. These results emphasize that agentic traits are valuable in terms of hiring and salary decisions when applying for a male-oriented position. Neither applicant sex nor sexual orientation impacted hiring or salary recommendations.